134 Improvements in Clinical Global Impression of Change With Deutetrabenazine Treatment in Tardive Dyskinesia From the ARM-TD and AIM-TD Studies. (15th June 2018) - Fernandez, Hubert H.; Davis, Mat D.; Factor, Stewart A.; Hauser, Robert A.; Jarskog, L. Fredrik; Jimenez-Shahed, Joohi; Kumar, Rajeev; Ochudlo, Stanislaw; Ondo, William G.; Anderson, Karen E.
Abstract: Introduction: Tardive dyskinesia (TD) is an involuntary movement disorder that is often irreversible, can affect any body region, and can be debilitating. In the ARM-TDand AIM-TD studies, deutetrabenazine treatment demonstrated statistically and clinically significant reductions in Abnormal Involuntary Movement Scale (AIMS) scores at Week 12 compared with placebo (primary endpoint). Objective: To evaluate the efficacy of deutetrabenazine, as measured by the Clinical Global Impression of Change (CGIC) scale, in patients with TD from the pooled ARM-TDand AIM-TD (24 and 36 mg/day doses) data sets, as compared with the pooled placebo cohort. Methods: ARM-TD and AIM-TD were 12-week, randomized, double-blind, placebo-controlled studies that evaluated the safety and efficacy of deutetrabenazine for thetreatment of TD. The key secondary endpoint of each study was the proportion of patients "much improved" or "very much improved" (treatment success) at Week 12 on theCGIC. Results: At Week 12, the odds of treatment success among patients treated with deutetrabenazine (n=152) was more than double that of patients given placebo (n=107; odds ratio: 2.12; P=0.005). In a categorical analysis of CGIC ratings, patients treated with deutetrabenazine showed greater improvement than patients given placebo (P=0.003). Patients treated with deutetrabenazine also had a significantly better treatment response than those given placebo (least-squares mean CGIC score treatment difference: –0.4; P=0.006). Conclusions: Deutetrabenazine treatment led to statistically and clinically significant improvements in TD symptoms based on the CGIC result, suggesting that clinicians were able to recognize the benefit in patients treated with deutetrabenazine. Presented at: The International Congress of Parkinson's Disease and Movement Disorders; June 4–8, 2017; Vancouver, British Columbia, Canada. Funding Acknowledgements: These studies were funded by Teva Pharmaceutical Industries, Petach Tikva, Israel.